The Development of Scrabble Game-Based Learning Media Using Javanese Script: Jable Board (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
Indonesia is the largest archipelagic country, consisting of thousands of islands, which causes Indonesia to have various types of diversity, one of which is the diversity of languages. Javanese is the most widely used regional language as a daily communication language among Indonesians. The distinctive feature of this language is that it has Javanese script. The government has introduced the Javanese script through learning Javanese in every school. However, the interest and curiosity of students are still relatively low. Moreover, the learning media used are also limited. Learning media is an important component in achieving the success of an optimal learning process. As a result, learning media should be able to become an effective and efficient channel of learning information, allowing students to easily comprehend what they are learning. Jable Board is the result of the development of learning media in Javanese script in the form of a scrabble game using Javanese script. The method used is the research and development method (Research and Development, or R&D) using the 4-D (four D) research model. From the product validation results, two types of data were obtained: qualitative data in the form of voice response, button accuracy, and battery life, as well as quantitative data in the form of a product-related questionnaire to teachers